Mining and floods: a systematic review of empirical studies on community resilience strategies and interventions - Mariam Bouzid; William J. Guerrero; Luz Elba Torres-Guevara; Dairo Steven Muñoz Pinzón; Carlos Daniel Montes Rodriguez; Lady Giovanna Rojas Pineda; Juan José Díaz Castro; Erika Cardona Patiño; Karol Elkjaer Mondragon Sanchez (The Extractive Industries and Society, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

Climate change drives agricultural land use competition in the Paranapanema River Basin, Southeastern Brazil - Argemiro Teixeira Leite-Filho; Érica Acioli Canamary; Anaí Floriano Vasconcelos; Daniel Andrés Rodriguez; Jaqueline Carolino Santos; Maria Clara Fava; Minella Alves Martins; Sara Bastos de Oliveira; Javier Tomasella (Land Use Policy, 2026)

ALVO: a collective platform for volcanic risk reduction in Latin America - Pablo Forte; Daniel Bertin; Lizzette Rodriguez; Mariana Patricia Jácome Paz; Silvana Hidalgo; Yemerith Alpizar-Segura; Guillermo E. Alvarado; Constanza Perales Moya; José Luis Palma; José G. Viramonte; Hugo Delgado-Granados (Journal of South American Earth Sciences, 2026)

Ant pruning and weak tussock facilitation jointly shape planted sapling performance along an elevation gradient - Daniel Renison; Juan Manuel Rodriguez; Santiago Costas; Niklas Heinemann; Isabell Hensen (Forest Ecology and Management, 2026)

Unveiling the Viral Landscape in Gastric Cancer - Diego Pereira; Fabiano Cordeiro Moreira; Daniel de Souza Avelar; Sérgio Augusto Antunes Ramos; Valéria Cristiane Santos da Silva; Jéssica Manoelli Costa da Silva; Ronald Matheus da Silva Mourão; Rubem Ferreira da Silva; Kauê Sant’Ana Pereira Guimarães; Juliana Barreto Albuquerque Pinto; Marcos da Conceição; Williams Fernandes Barra; et al. (Current Microbiology, 2026)
The present study aimed to comprehensively characterize the cancer-associated virome in patients with gastric cancer. A total of 452 samples were analyzed, including 226 tumor tissues and 202 peritumoral tissues from patients undergoing surgical resection, alongside 24 normal gastric mucosa samples obtained via endoscopy from individuals without cancer. RNA was extracted, libraries were prepared, and paired-end sequencing was performed on the NextSeq 500 platform (Illumina, US). High-quality reads were processed with Kraken2, using the standard database supplemented with the Reference Viral Database, to identify viral taxa. Taxonomic profiles, differential viral abundance, and alpha and beta diversity metrics were computed in RStudio, with statistical analyses performed to compare viral composition and diversity among tissue groups using Kruskal-Wallis, Wilcoxon, PERMANOVA, and PERMDISP tests ( p

Corrigendum to “Reassessment of the Holocene eruptive history of Atitlán stratovolcano, Guatemala” [J. South Am. Earth Sci. (2026) 105973] - Eduard Pico Rodriguez; Lucia Capra; Rafael Torres-Orozco; Daniel Eduardo Secaira Ziegler; Gustavo Adolfo Chigna Marroquín; María Moncada Vásquez (Journal of South American Earth Sciences, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Prevalent detection of multiclass environmental chemicals in paired CSF and plasma samples and their potential associations with postpartum depressive symptoms in pregnant women - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Hiraj Patel; Daniel Katz; Joshua Hamburger; Noel Strong; Leah Habersham; Anna-Sophie Rommel; Lotje D. de Witte; Chris Gennings; M Mercedes Perez-Rodriguez; et al. (Environmental Research, 2026)

Etiology of Chickpea Yellowing Syndrome (CYS) in Argentina: the role of fungal and viral pathogens - Bruno Daniel Pugliese; Patricia Rodriguez Pardina; Juan Pablo Edwards Molina; Sebastián Alberto Stenglein; Silvina Pastor (European Journal of Plant Pathology, 2026)

Methionine Enhances Growth and Stress Tolerance in Tomato Seedlings under Salinity Stress - Murat Aydin; Selda Ors Cirik; Melek Ekinci; Sümeyra Ucar; Esra Yaprak; Esma Yigider; Ertan Yildirim; Metin Turan; Aysegul Kasapoglu; Daniel Rodriguez-Leal (Journal of Plant Growth Regulation, 2026)

Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.

In silico and experimental characterization of fipronil–membrane interactions: Implications for pesticide selectivity - Marcos A. Asis-Rodriguez; Mariela E. Sánchez-Borzone; Daniel A. García; Virginia Miguel (Pesticide Biochemistry and Physiology, 2026)

Application of a non-destructive methodology for determining the thickness of oblique cones - Daniel de Castro Maciel; Rafael Nunes Sigales; Naábia Kamila Gomes Guedes; Gilmar Cordeiro Silva; Alejandro Martins Rodriguez; Aline Soares Pereira (Next Research, 2026)

Spatiotemporal dynamics, components, and drivers of virtual water flows for grain crops in China - Jiongchao Zhao; Yixuan Wang; Daniel Rodriguez; Mingyu Zhao; Yupeng Feng; Xiaoyu Shi; Tong Han; Jie Lu; Fu Chen; Qingquan Chu (Regional Environmental Change, 2026)

Monte Carlo modelling of the AKR-2 training and research reactor - Juan José Gómez Rodriguez; Alexander Knospe; Marco Viebach; Sebastian Hübner; Thibault Saalfeld; Vincent Melzer; Sascha Weichel; Daniel Gehre; Antonio Hurtado; Carsten Lange (Annals of Nuclear Energy, 2026)

Metformin promotes healthspan by attenuating frailty and preserving musculoskeletal function–structure in middle-aged mice - Diego Armando Morales-Carrizales; Daniel Garza-Guzman; Maria de Jesus Loera-Arias; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha (Biogerontology, 2026)

IoT-enabled air quality prediction using ensemble machine learning: a case study in San Salvador, El Salvador - Josue Ramirez-Ramirez; Daniel Amaya-Cruz; Griselda Zepeda-Navarro; Bayron Carpio-Villaran; Miguel Alfaro-Vides; Yakdiel Rodriguez-Gallo; Omar Otoniel Flores-Cortez; Carlos Osmín Pocasangre Jiménez; Werner David Meléndez (Air Quality, Atmosphere & Health, 2026)

Influence of picloram and BAP on callus cultures for vindoline synthesis in Catharanthus roseus - Karen Jennifer Gonzalez-Osorio; María Guadalupe Aguilar-Uscanga; María Inés Infanzón-Rodríguez; Javier Gomez-Rodriguez; Daniel Arturo Zavala-Ortiz (Vegetos, 2026)

Ambient temperature and homicide mortality in 307 Latin American cities: A case time series design - Sara Lopes de Moraes; Daniel A. Rodriguez; Leah H. Schinasi; Josiah L. Kephart; Iryna Dronova; Maryia Bakhtsiyarava; Waleska Teixeira Caiaffa; Karla Rangel-Moreno; Laura A. Rodriguez-Villamizar; Marie O'Neill; Amélia Augusta de Lima Friche; Astrid Berena Herrera López; et al. (Environmental Research, 2026)

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

Correction: Etiology of Chickpea Yellowing Syndrome (CYS) in Argentina: the role of fungal and viral pathogens - Bruno Daniel Pugliese; Patricia Rodriguez Pardina; Juan Pablo Edwards Molina; Sebastián Alberto Stenglein; Silvina Pastor (European Journal of Plant Pathology, 2026)

(Poly)phenol metabotypes and cardiometabolic health: a systematic review - Wafa Alotaibi; Daniel Perrone; Xiaohe Liu; Celeste Lugtmeijer; James Pham; Selena Wu; Sara Dorottya Biro; Shradha Gurung; Wendy L. Hall; Ana Rodriguez-Mateos (Critical Reviews in Food Science and Nutrition, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Reassessment of the Holocene eruptive history of Atitlán stratovolcano, Guatemala - Eduard Pico Rodriguez; Lucia Capra; Rafael Torres-Orozco; Daniel Eduardo Secaira Ziegler; Gustavo Adolfo Chigna Marroquín; María Moncada Vásquez (Journal of South American Earth Sciences, 2026)

Spatial Modeling of Sugarcane Yield Using Machine Learning Approaches - Diego A. Socadagui-Casas; Andres F. Rodriguez-Vasquez; Yolanda Rubiano-Sanabria; Daniel M. Jimenez-Gutierrez; Sonia R. Socadagui-Casas (Sugar Tech, 2026)
Sustainable precision agriculture and artificial intelligence (AI) are transforming modern farming by enhancing resource efficiency, addressing climate challenges, and fostering sustainability. In Colombia, sugarcane cultivation is pivotal in the agricultural economy, particularly in the Cauca River Valley, a region grappling with climate variability and resource optimization challenges. This study introduces an innovative methodology that combines machine learning (ML) techniques with geospatial data to predict sugarcane yields accurately. The research employs the CatBoost, random forest, and XGBoost ML algorithms, integrating historical data on climate, soil characteristics, and agricultural management practices to develop spatially detailed predictive models. The findings demonstrate that ML-based approaches outperform traditional methods like linear and penalized regressions, offering more precise agricultural planning and resource management predictions. Focused on the municipality of La Candelaria, this work underscores the potential of ML technologies to enhance productivity while promoting sustainable agriculture.

Recirculated submarine groundwater discharge dominates nutrient inputs and enhances eutrophication risk in a coastal lagoon - Júlia Rodriguez‐Puig; Clara Ruiz‐González; Marc Diego‐Feliu; Irene Alorda‐Montiel; Aaron Alorda‐Kleinglass; Daniel Romano‐Gude; Andrea G. Bravo; Júlia Dordal‐Soriano; Javier Gilabert; Sophia Bergeler; Céline Lavergne; Gemma Casas; et al. (Limnology and Oceanography, 2026)
Submarine groundwater discharge (SGD) is a widely recognized pathway for nutrient transport to coastal systems. Prior studies overlook the unique biogeochemical signatures of different SGD pathways, neglecting their differences in biogeochemical transformations and spatiotemporal factors. Here, we present an integrated assessment of nutrient delivery through three SGD pathways (fresh SGD, long‐scale recirculated SGD, and short‐scale porewater exchange), alongside surface water inputs, to evaluate their seasonality and impact on nutrient dynamics in a coastal lagoon. We conducted five field surveys in March, July, and November 2021, July 2024, and March 2025 in the Mar Menor lagoon, an ecosystem facing severe ecological degradation, to analyze nutrient concentrations in stream water, groundwater, and lagoon water. Concentrations in discharging waters were shaped by watershed‐scale land use and local redox‐driven biogeochemical processes. Recirculated SGD (long‐scale and short‐scale), often overlooked, emerged as the dominant source of ammonium (; 100–160 kmol d −1 ), dissolved organic nitrogen (DON; 270–900 kmol d −1 ), dissolved inorganic phosphorus (DIP; 4–30 kmol d −1 ), and dissolved silica (DSi; 200–270 kmol d −1 ) across seasons, while continental discharge (streams and fresh SGD) was the main source of nitrate and nitrite (NO x ; 30–210 kmol d −1 ). Short‐scale recirculation flows controlled seasonal nutrient limitation by delivering additional DIP inputs (24 kmol d −1 ) in summer, increasing eutrophication risk. Identifying preferential transport pathways for each nutrient into coastal systems is crucial for predicting and managing ecosystem vulnerability.

Decoupled Climatic Drivers of Tree and Ground‐Layer Carbon Uptake in Mountain Ecosystems Around the World - Max Mallen‐Cooper; Maja K. Sundqvist; David A. Wardle; Radim Šarlej; Rose E. Brinkhoff; Aimée T. Classen; Eliška Kuťáková; Daniel B. Metcalfe; M. Noelia Barrios‐Garcia; Julie R. Deslippe; Kobayashi Makoto; Jane Mallen‐Cooper; et al. (Global Change Biology, 2026)
One of the key ecological processes affected by climate change is plant carbon uptake. However, there is substantial uncertainty about how plant carbon uptake will respond to warming in mountain ecosystems, which are known for sharp temperature gradients and abrupt shifts in vegetation structure. Specifically, we lack an understanding of whether these response trajectories over time will be linear or non‐linear, and how they might vary among mountain ecosystems globally. Here, we measured ecosystem Gross Primary Productivity (GPP) along forest‐tundra elevational gradients in the mountain regions of five countries (Argentina, Australia, France, Sweden, USA) to infer future trajectories of carbon uptake, and whether any non‐linear changes might occur. We also examined the role of microclimate in driving GPP responses. We found that whole‐ecosystem GPP increased with increasing macroclimatic temperature (decreasing elevation), but this response was dominated by a sharp non‐linear increase at the transition from tundra to forest (i.e., the treeline). In contrast, ground‐layer GPP was largely independent of macroclimate, but often responded strongly, and linearly, to microclimate (growing degree days > 5°C, mean growing season temperature). This pattern reflected a frequent decoupling of microclimate from the expected temperature‐elevation relationship, likely driven by such processes as cold‐air drainage, limited near‐surface air mixing, and shading by trees. The contrasting responses of GPP among global temperature gradients indicates strong context dependence at both local and continental scales, although in a few cases, biomass and leaf nitrogen were important moderators. These findings suggest that future shifts in carbon uptake in mountains will be mainly controlled by tree range expansion. Our results highlight the need to consider species responses on different spatial scales, and to increase representation of undersampled regions to capture the full breadth of ecological responses to climate change.

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Indirect exposure to organophosphate pesticides and its possible growth disorders in children of farmers in Northwest Mexico - Estefanía Ochoa-Ruiz; Aarón Israel Moreno-García; Daniel Alejandro Licea-Espinoza; Gisela Pineda-García; Krysta Paola Carranza-Ambriz; Kenya Karina Soto-Rodriguez; Arnold García-Ledezma; José Manuel Cornejo-Bravo; Ana Laura Martínez; Eleonora Mondani; Aracely Serrano-Medina (International Archives of Occupational and Environmental Health, 2026)
Purpose This study investigated the correlation between growth disorders and indirect pesticide exposure in children of farmers. Methods A cross-sectional study was conducted with 134 children of farmers occupationally exposed to organophosphate pesticides in the ejido Venustiano Carranza, an agricultural community in San Quintín, Baja California, Mexico. These children were compared with a control group of 56 unexposed children. Anthropometric measurements and biochemical analyses were performed in both groups to evaluate renal, hepatic, and nutritional profiles. Hormonal profiles were quantified using ELISA techniques. Cholinesterases are quantified using known colorimetric methods. Food security was also analyzed through a dietary diversity study, focusing on households. Results Indirectly exposed group showed a higher prevalence of stunting (18% vs. 16.4%) than controls. Food safety was adequate in both groups (X 2 = 1.88, p = 0.597). The indirectly exposure children showed significantly higher calcium levels (9.99 ± 0.63 mg/dL) and significant increases in liver enzymes AST and GGT ( p < 0.001). ALP was 1.5 times lower than in unexposed children ( p < 0.001), showing a strong association with exposure time ( p = 0.009). The indirectly exposed group showed lower GH and IGF-1 levels; 2.55 and 1.28 times lower than in controls, respectively. Children with indirect exposure showed a significant reduction in AChE (7211 ± 1917 vs. 8368 ± 213 U/L, p < 0.001) and an even greater decrease in BChE (6426 ± 1664 vs. 8025 ± 1462 U/L, p < 0.001). Conclusion This work demonstrates an association between environmental exposure to organophosphate pesticides and children's growth and provides crucial insights for future research and policymaking.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Investigating Blast-Induced Damage: A Comprehensive Study of Crack Development Profiles Under Decoupled Charges - Carlota Rodriguez-San Miguel; Changping Yi; Nikolaos Petropoulos; Daniel Johansson (Rock Mechanics and Rock Engineering, 2026)
In mining, tunneling, and other blasting applications, excessive rock fracturing can compromise stability and deteriorate environmental and economic outcomes. Predicting the extent of blast-induced cracks is critical to accurately assess structural damage and optimize blast design. Seven blast tests were performed on 150 × 300 mm cylinders with a central blasthole of 280 mm length. PETN cord (5 g/m) was used, and the decoupling ratios ( f ) of 2.5, 4.2, and 5.0 were achieved by varying the blasthole diameters. In this study, qualitative and quantitative aspects of the induced cracks (number, type, velocities, propagation patterns, etc.) were examined using ultra-high-speed (UHS) photography and 2D Digital Image Correlation (DIC) method. Numerical modeling with LS-DYNA was conducted to simulate the experiments, to expand the analysis from 2D to 3D. The experimental results showed that crack initiation, gas ejection, and damage level decreased when increasing the decoupling ratio; notably, no damage occurred when f = 5. Crack propagation velocity using the DIC results showed $$\overline{V _{c}}$$ V c ¯ = (839.40 ± 46.57) m/s. A model for $${V}_{c}$$ V c from the experimental results was established through curve fitting with a $${R}^{2}$$ R 2 > 97%. The DIC analysis enabled the distinction of the fracture process zone and the crack tip location. The numerical modeling results provided a realistic estimation of the cracks and damage compared to the experiments. The experimental and numerical results show that increasing the decoupling ratio reduces qualitative and quantitatively the blast-induced cracks, demonstrating how blast-induced damage could be limited.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Forecasting the Biological Effect of PEGylated-rHuEPO Candidates in Chronic Kidney Disease Patients using a Middle-out Translation Approach - Gledys Reynaldo-Fernandez; Leyanis Rodriguez-Vera; Daniel Amaro; Joaquin Solozábal; Jorge Duconge; Victor Mangas-Sanjuan; Iñaki F. Troconiz; Francine Johansson Azeredo; Valvanera Vozmediano (Pharmaceutical Research, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Salt dust storms from the Mar Chiquita Lagoon (Argentina): 20-year occurrence analysis and WRF-Chem modeling of PM10 distribution in selected case studies - Mariana Renee Pagot; Franco Javier Dimari; Román Gustavo Martino; Gerardo Daniel Hillman; Jonathan Muchiut; Eduardo Gabriel López; Brian Enrique del Valle Pucheta; Roberto Carlos Pepino Minetti; Andrés Rodriguez (Environmental Monitoring and Assessment, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Optical and random laser properties of the novel multifunctional endoxifen derivative (FLTX3) and its potential for the diagnosis of breast cancer resistance - Mario Diaz; Sergio de Armas-Rillo; Fernando Lobo; Daniel Pereda de Pablo; Kevin Soler-Carracedo; Pablo Delgado; Mitzi Rodriguez; Ana Canerina-Amaro; Catalina Valdes-Baizabal; Raquel Marín; Dácil Hernández; Alicia Boto; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Effect of Probiotics on Sperm Quality in the Adult Mouse - Ana Sanchez-Rodriguez; Ingrid I. D. Idrovo; Rocío Villafranca; Nerea Latorre; Juan Antonio Rielo; Ane Laburu; Sandra Nieto-Román; Daniel Heredia; Rubén González; Virginia García-Cañas; Diego Laxalde; Carolina Simó; et al. (Probiotics and Antimicrobial Proteins, 2025)
The administration of probiotics for the treatment of different diseases has gained interest in recent years. However, few studies have evaluated their effects on reproductive traits. The objective of this study was to examine the effect of two mixtures of probiotics, a commercial probiotic (Vivomixx®) and a mix of Lacticaseibacillus rhamnosus GG and Faecalibacterium duncaniae A2-165, on sperm quality in a mouse model. Adult male mice (8 months old) were used for two experimental and one control groups ( n = 5 each). The probiotics or physiological serum (control) was administered orally, twice a week, during 5 weeks. Sperm were collected from the cauda epididymis, and their total number, motility, kinematics, morphology, and acrosome integrity were assessed in recently collected samples and after a 60-min in vitro incubation. Results showed a higher percentage of normal sperm in both experimental groups, with fewer head abnormalities than in the control. Differences were found among groups in the morphometry of sperm heads, being more elongated in mice treated with probiotics. Sperm from probiotic-treated mice showed similar total motility when compared to the controls, although the proportion of progressively moving sperm and their vigor of motility were lower. Sperm swimming descriptors were measured with a CASA system. Velocity parameters were similar among groups whereas linearity was higher in mice treated with the commercial probiotic. These results suggest that the administration of probiotics may increase the proportion of sperm with normal morphology and lead to modifications in sperm head shape that may enhance sperm swimming. Studies using a longer administration period would be useful in further characterizing the effect of these probiotic mixtures on sperm quality and fertilization capacity.

Impact of Submarine Groundwater Discharge on Microbial Communities in a Highly Anthropized Coastal Lagoon (Mar Menor, SE Spain) - Daniel Romano‐Gude; Júlia Dordal‐Soriano; Júlia Rodriguez‐Puig; Andrea G. Bravo; Irene Alorda‐Montiel; Aaron Alorda‐Kleinglass; Marc Diego‐Feliu; Cristina Romera‐Castillo; Rebeca Mallenco‐Fornies; Javier Gilabert; Jordi Garcia‐Orellana; Valentí Rodellas; et al. (Molecular Ecology, 2025)
Submarine groundwater discharge (SGD) supplies large quantities of nutrients and other terrestrial elements to coastal ecosystems, impacting marine biota and ecosystem functioning. Despite the relevance of prokaryotes for marine biogeochemistry, little is known about their responses to groundwater inputs. Here we explored the impact of SGD on the spatiotemporal patterns of prokaryotic communities from the Mar Menor (Murcia, Spain), a highly anthropized hypersaline coastal lagoon that receives large amounts of nutrient‐polluted SGD. Using 16S rRNA amplicon sequencing, activity assays, and flow cytometry, we investigated the dynamics of prokaryotic communities across the lagoon and its connected environments (freshwater streams, groundwater, soils, the sea) on two occasions. We found that the lagoon areas most influenced by SGD (i.e., sites closest to the shore) presented on average three‐fold higher heterotrophic prokaryotic protein production than the inner lagoon samples, and 2.7‐fold higher taxonomic richness. This spatial pattern was likely influenced by solutes supplied by SGD, as higher concentrations of dissolved nitrogen, silicate and SGD tracers (radium [Ra] isotopes) were found in nearshore waters. Increases in these elements also influenced the relative abundance of dominant bacterial groups (e.g., Flavobacteriales, Rhodobacterales). In autumn, increases in lagoon 224 Ra were strongly linked to higher taxonomic richness in microbial assemblages and the influx of allochthonous taxa from the catchment, pointing to seasonally variable transport of coastal groundwater microorganisms via SGD. Our study highlights SGD as an overlooked driver of prokaryotic dynamics in coastal ecosystems, and suggests that changes in this process may significantly impact microbial community structure and functioning.

A Bayesian network and DEMATEL-ISM based approach for evaluating resilience: A case study in inland waterway port - Fernando Gonzalez-Solano; Gina Galindo; Daniel Romero-Rodriguez (Ocean & Coastal Management, 2025)

Transgene-free genome editing in citrus and poplar trees using positive and negative selection markers - Dhiôvanna Corrêia Rocha; Miracle Osazee Omoregbee; Danyel Fernandes Contiliani; Rushil Mandlik; Gen Li; Juliet Mascoveto; Gary Coleman; James N. Culver; Daniel Rodriguez Leal; Alessandra Alves de Souza; Yiping Qi (Plant Cell Reports, 2025)
Key message Transgene-free genome editing of the gene of interest in citrus and poplar has been achieved by co-editing the ALS gene via transient transgene expression of an efficient cytosine base editor. Abstract CRISPR-Cas genome editing systems have been widely used in plants. However, such genome-edited plants are nearly always transgenic in the first generation when Agrobacterium -mediated transformation is used. Transgene-free genome-edited plants are valuable for genetic analysis and breeding as well as simplifying regulatory approval. It can be challenging to generate transgene-free genome-edited plants in vegetatively propagated or perennial plants. To advance transgene-free genome editing in citrus and poplar, we investigated a co-editing strategy using an efficient cytosine base editor (CBE) to edit the ALS gene to confer herbicide resistance combined with transient transgene expression and potential mobile RNA-based movement of CBE transcripts to neighboring, non-transgenic cells. An FCY-UPP based cytotoxin system was used to select non-transgenic plants that survive after culturing on 5-FC containing medium. While the editing efficiency is higher in poplar than in citrus, our results show that the CBE-based co-editing strategy works in both citrus and poplar, albeit with low efficiency for biallelic edits. Unexpectedly, the addition of the TLS mobile RNA sequence reduced genome editing efficiency in both transgenic and non-transgenic plants. Although a small fraction of escaping plants is detected in both positive and negative selection processes, our data demonstrate a promising approach for generating transgene-free base-edited plants.

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

Pathways towards Net Zero emissions in grain cropping farms - Zhihao Tan; Peter de Voil; Jiongchao Zhao; Dongxue Zhao; Hamish McGowan; Liujun Xiao; Daniel Rodriguez (Agricultural Systems, 2025)

Splenomegaly, Spleen Amyloidosis and Neutrophil Infiltration are Present in 3xTg-AD, but not Tg-SwDI Mice - Gonzalo Acero; Adrian Rodriguez-Lopez; Georgina Díaz; Daniel Esteban; Mónica Herrera-Ángeles; Goar Gevorkian (NeuroMolecular Medicine, 2025)
It is now widely accepted that the development of neurodegenerative diseases depends on and affects many pathological processes, both in the brain and the periphery. Inflammatory, cardiovascular, metabolic, cerebrovascular, autoimmune, and other environmental factors have been extensively studied and shown to contribute notably to the onset, pathogenesis, and clinical outcome of Alzheimer´s disease (AD), Parkinson´s disease (PD), cerebral amyloid angiopathy (CAA), multiple sclerosis, and other neurological disorders. Likewise, AD-induced changes in other tissues outside the central nervous system, such as abnormalities observed in the liver, spleen, or lungs, have been documented and extensively studied, leading to a better understanding of brain-periphery crosstalk in neurodegenerative diseases and the development of novel diagnostic and therapeutic approaches. In this study, we documented striking differences in the periphery in two frequently used, well-established APP transgenic mouse models of AD: 3xTg-AD mice, harboring three human genes (APP, tau, and Psen1), and Tg-SwDI mice, expressing human APP with the Swedish and vasculotropic Dutch/Iowa mutations in the brain. We documented splenomegaly, immunoglobulin-associated spleen amyloidosis, and an increase in the percentage of neutrophils in the spleen and macrophages in the liver in 3xTg-AD mice but not in age-matched Tg-SwDI mice, which are commonly used as an AD/CAA model. Our data suggest that the results observed in any transgenic mouse strain should be taken into account with caution. A detailed knowledge of pathological characteristics recapitulated in a particular strain can help to determine which mice are more appropriate for studying a specific mechanism or therapeutic approach.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Tree survival and growth in the highlands of central Argentina: Impact of wildfires and land management - Daniel Renison; Iván Barberá; Ana M. Cingolani; Juan Manuel Rodriguez; Isabell Hensen (Forest Ecology and Management, 2025)

Correction to: Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández‑Pérez; Joan Jiménez‑Balado; Adrià Macias‑Gómez; Antoni Suárez‑Pérez; Marta Vallverdú‑Prats; Alberto Pérez‑Giraldo; Marc Viles‑García; Julia Peris‑Subiza; Sergio Vidal‑Notari; Eva Giralt‑Steinhauer; Daniel Guisado‑Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

The plasticity of root traits and their effects on crop yield and yield stability - Dongxue Zhao; Peter de Voil; Victor O. Sadras; Jairo A. Palta; Daniel Rodriguez (Plant and Soil, 2025)
Context Phenotypic plasticity can be a valuable adaptation strategy for coping with environmental heterogeneity. There is limited information on the plasticity of root traits and their effect on yield and yield stability. Objectives With a perspective of phenotypic plasticity, we focus on functional root traits associated to water uptake in field-grown sorghum to answer: (i) How do genetic (G), environmental (E) and management (M) factors and their interactions, affect the root traits? and (ii) How do root traits and their plasticity affect yield and yield stability? Methods A new high-throughput functional root phenotyping approach was used in G × E × M trials to quantify two root traits, maximum rooting depth (MxRD) and a root activity index (RAindex). Crop phenotypic plasticities were determined using the reaction norm method. Results The applied G × E × M treatments created plastic responses between the tested hybrids. There was a hierarchy of plasticities for the different traits studied i.e., grain number traits > root traits > grain weight traits. The plasticity of root traits was associated with the stability of grain yield traits. Hybrids with high root plasticity tend to have more stable grain numbers and grain weights. Conclusions There is valuable genetic diversity in the mean value and plasticity of root traits that could be used to match root phenotypes to target production environments. Our root phenotyping approach can be a valuable tool for understanding the dynamic interactions between root function, root architecture and yield traits in the field under variable environments.

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Consequential life cycle assessment of pretreatment strategies for a microalgae-based wastewater treatment pilot unit in a circular livestock industry bioeconomy - Anaid López-Sánchez; Carlos Daniel García-López; Gary Ossmar Lara-Topete; Juan Daniel Castanier-Rivas; Paloma Barajas-Álvarez; Martín Esteban González-López; Ana Laura Silva-Gálvez; Hongying Zhou; Christopher Q. Lan; Carlos Eduardo Robles-Rodriguez; Samir Meramo-Hurtado; Misael Sebastián Gradilla-Hernández (Algal Research, 2025)

Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández-Pérez; Joan Jiménez-Balado; Adrià Macias-Gómez; Antoni Suárez‑Pérez; Marta Vallverdú-Prats; Alberto Pérez-Giraldo; Marc Viles-García; Julia Peris-Subiza; Sergio Vidal-Notari; Eva Giralt-Steinhauer; Daniel Guisado-Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Synergies Between Agricultural Production and Shorebird Conservation With Climate Change in the Central Valley, California, With Optimized Water Allocation and Multi‐Benefit Land Use - Liying Li; Spencer Cole; José M. Rodriguez‐Flores; Erin Hestir; Daniel Fink; Joshua H. Viers; Josue Medellin‐Azuara; Martha Conklin; Thomas Harmon (Global Change Biology, 2025)
Conservation planning that enhances the resiliency of biodiversity to climate change requires adaptive water and land use decision‐making in the most cost‐efficient way. This has many challenges since landscapes with high biodiversity can embrace intense human production activities, particularly agriculture. Conventionally, water and land used for conservation are often regarded as tradeoffs to agricultural productivity. However, this study found that agricultural water and land use synergize with shorebird conservation in the Central Valley, California. If informed decisions are made to guide strategic land use, landscapes can adapt to climate change and offer multiple benefits. This study used a coupled economic optimization model with a species distribution model to consider human factors in ecological impacts. The objective was to assess the impacts of agricultural water and land use decisions under different climate change scenarios on 10 shorebird species populations in California's Central Valley. Our results showed that strategic water and land management can offer favorable habitats to targeted shorebirds with a land composition including diversified crop categories complementary to wetlands. This study demonstrates that agricultural lands can be as important as wetlands to shorebirds to sustain their migratory stages throughout the year. Wetland restoration without species habitat preference information can lead to population shrinkage since wetland types vary in habitat importance to the shorebird species studied in this research. Business as usual, along with land use and climate change, will decrease shorebirds' breeding season and population to the same degree as they impact non‐breeding populations. The synergies between agricultural production and shorebird conservation were found in the scenarios that favor agricultural production water use but also favor habitat provisioning to shorebirds in the Central Valley, California, under climate change.

Spatiotemporal assessment and monitoring of urban heat islands in metropolitan areas using machine learning and downscaling - Rafael João Sampaio; Daniel Andrés Rodriguez; Rogério Pinto Espíndola; Fabricio Polifke da Silva (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Nutritional ketosis modulates the methylation of cancer-related genes in patients with obesity and in breast cancer cells - Paula M Lorenzo; Andrea G Izquierdo; Gemma Rodriguez-Carnero; Nicolas Costa-Fraga; Angel Díaz-Lagares; Cristina Porca; Daniel de Luis; Cristina Tejera; Laura De Paz; Juan Cueva; Diego Bellido; Ana B Crujeiras (Journal of Physiology and Biochemistry, 2025)
Scientific evidence demonstrates that a very low-calorie ketogenic diet (VLCKD) is effective and beneficial in the treatment of obesity, capable of reversing the methylome associated with obesity and has immunomodulatory capacity. This effect is in part promoted by nutritional ketosis and could be involved in counteracting obesity-related cancer. The aim of this study was to evaluate the effect of nutritional ketosis on the methylation of genes related to tumor processes in patients with obesity and in breast cancer cells. Based on methylome data (Infinium MethylationEPIC BeadChip, Illumina) from patients with obesity treated with a VLCKD for weight loss ( n = 10; n = 5 women, age = 48.8 ± 9.20 years, BMI = 32.9 ± 1.4 kg/m2), genes belonging to cancer-related pathways were specifically evaluated and further validated in vitro in MDA-MB-231 (triple negative) and MCF7 (RE positive) breast tumor cells pretreated for 72 h with βOHB, the main ketone body, secretome from visceral (VATs) or subcutaneous (SATs) adipose tissue of patients with obesity. The cell tumoral phenotype was evaluated by proliferation assay and expression of cancer-related genes. VLCKD-induced nutritional ketosis promoted changes in the methylation of 18 genes (20 CpGs; 17 hypomethylated, 3 hypermethylated) belonged to cancer-related pathways with MAPK10, CCN1, CTNNA2, LAMC3 and GLI2 being the most representative genes. A similar pattern was observed in the MDA-MB-231 cells treated with β-OHB, without changes in MCF7. These epigenetic changes paralleled the tumoral phenotype modulated by the treatments. Taking together these results highlight the potential role of VLCKD as an adjuvant to anticancer treatment in groups more susceptible to the development of cancer such as patients with obesity, exerting epigenetic regulation through nutritional ketosis and weight loss.

Benefits and trade-offs from the diversification of rangeland farms in Northern Queensland, Australia - Lipy Adhikari; Peter de Voil; M. Fernanda Dreccer; Daniel Rodriguez (Agricultural Systems, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Occupational Health and Safety Concerns for Hookah Divers in Small-Scale Fisheries in the Gulf of California, Mexico - Carlos Acevedo-Rodriguez; Jorge Torre; Polo Barajas-Girón; Raziel Elihu Hernández-Pimienta; Imelda G. Amador-Castro; Daniel Valdez (Journal of Agromedicine, 2025)

Insomnia accelerates the epigenetic clocks in older adults - Nadia Alejandra Rivero-Segura; Julian Daniel Rodriguez Cuartas; Paola Garcia-delaTorre; Sergio Sanchez-Garcia; Ricardo Ramirez-Aldana; Juan Carlos Gomez-Verjan (GeroScience, 2025)

Innovative mobilities - Haotian Zhong; Peng Chen; Daniel Rodriguez-Roman; Erick Guerra (Transportation Research Part D: Transport and Environment, 2025)

Characterization and Differential Expression of Sex Genes in Adults of Tropical Gar (Atractosteus tropicus) - Otilio Méndez-Marin; María de Lourdes Jiménez-Badillo; Carina Shianya Álvarez-Villagomez; Talhia Martínez-Burguete; Uriel Rodriguez-Estrada; Gloria Gertrudys Asencio-Alcudia; Graciela María Pérez-Jiménez; Gabriela Galindo-Cortés; Virgilio Eugenio Arenas-Fuentes; Rafael Martínez-García; Luis Daniel Jiménez-Martínez; Carlos Alfonso Alvarez-González (Fishes, 2025)
The tropical gar (Atractosteus tropicus) is a primitive freshwater fish of significant commercial importance in southeastern Mexico. However, its population is in danger due to habitat loss and overexploitation. Cultivation emerges as a viable reproductive management strategy; yet further studies are crucial to understanding molecular markers guiding reproductive management, differentiation, and sexual maturation in this species. We analyzed the expression of five sex-related genes (foxl2, sox9, cyp17a1, dmrt1, and cyp19a1) in the brain, liver, and gonads of adult A. tropicus (four females and five males). Methodologically, we collected samples and conducted RNA extraction, cDNA synthesis, and gene expression analysis using qPCR. The gonadal histology provided morphological context that reveals that the differential expression of genes establishes differences between sexes. The sexual phenotype of females is observed with the high expression of dmrt1, while in males, there is a reduction in the expression of dmrt1 and high levels of sox9, foxl2, and cyp17a1. Our findings establish dmrt1 and cyp19a1 as potential sex biomarkers and provide a molecular basis for developing sexing protocols in A. tropicus.

Assessing the impact of the new Mexico cable car on air pollution - Juan Prieto-Rodriguez; Jose Ignacio Azuela-Flores; Daniel Groft; Maria Jose Perez-Villadoniga; Rafael Salas (Journal of Transport Geography, 2025)

The diurnal variation of dust and water ice aerosol optical depth at Jezero crater observed by MEDA/TIRS over a full Martian year - Michael D. Smith; Germán M. Martínez; Eduardo Sebastián; Mark T. Lemmon; Samuel A. Atwood; Daniel Toledo; Daniel Viúdez-Moreiras; Aurélien Stcherbinine; Jose Antonio Rodriguez-Manfredi; Manuel de la Torre Juárez (Icarus, 2025)

Trustworthiness: an adaptationist account - Laureon A. Merrie; Jaimie Arona Krems; Daniel Sznycer; Nina N. Rodriguez (Evolution and Human Behavior, 2025)

A review of the venom microbiome and its utility in ecology and evolution including future directions for emerging research - Marina E. De León; Eduardo G. P. Fox; Sara Dunaj; Ronald A. Jenner; Carl N. Keiser; Jason Macrander; Samantha A. Nixon; Clarissa J. Nobile; Daniel Petras; Eduardo Rodriguez-Roman; Anthony J. Saviola; Steven A. Trim; et al. (Symbiosis, 2025)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Optimization of the stowage of fishing discards: Innovations in trawlers in the Gulf of Cadiz (SW Iberian Peninsula) - Daniel J. Coronil-Huertas; Carlos Rodriguez-García; Santiago Pavón-Quintana; Juan M. Vidal-Pérez; Jésica Sarmiento-Carbajal; Remedios Cabrera-Castro (Regional Studies in Marine Science, 2024)

Agronomic adaptations to heat stress: Sowing summer crops earlier - Daniel Rodriguez; Loretta Serafin; Peter de Voil; Michael Mumford; Dongxue Zhao; Darren Aisthorpe; Jane Auer; Ian Broad; Joe Eyre; Mark Hellyer (Field Crops Research, 2024)

Sowing summer grain crops early in late winter or spring: effects on root growth, water use, and yield - Dongxue Zhao; Peter deVoil; Bethany G. Rognoni; Erin Wilkus; Joseph X. Eyre; Ian Broad; Daniel Rodriguez (Plant and Soil, 2024)
Context Drought and extreme heat at flowering are common stresses limiting the yield of summer crops. Adaptation to these stresses could be increased by sowing summer crops early in late winter or early spring, to avoid overlap of drought and heat with critical crop stages around flowering. Though little is known about the effects of cold weather on root growth, water use and final grain yield in sorghum. Objective This study aims to explore the effects of cold conditions in early sowing sorghum on crop and root growth and function (i.e., water use), and final grain yield. Methods Two years of field experiments were conducted in the Darling and Eastern Downs region of Qld, Australia. Each trial consisted of three times of sowing (late winter, spring, and summer), two levels of irrigation (i.e., rainfed and supplementary irrigated), four plant population densities (3, 6, 9 and 12 pl m −2 ), and six commercial sorghum hybrids. Roots and shoots were sampled at the flag leaf stage on three times of sowing, two levels of irrigation, and three replications, for a single hybrid and a single plant population density (9 pl m −2 ). Crop water use and functional root traits were derived from consecutive electromagnetic induction (EMI) surveys around flowering. At maturity crop biomass, yield and yield components were determined across all treatments. Results The combinations of seasons, times of sowing and levels of irrigation created large variations in growth conditions that affected the growth and production of the crops. Early sowing increased yield by transferring water use from vegetative to reproductive stages and increasing grain numbers in tillers. Cold temperatures in the early sowing times tended to produce smaller crops with smaller rooting systems, smaller root-to-shoot ratios, and larger average root diameters. Total root length and root length density increased with increasing pre-flowering mean air temperatures up to 20 °C. Linear relationships were observed between an EMI derived index of root activity and the empirically determined values of root length density (cm cm −3 ) at flowering. Conclusions Sowing sorghum, a summer crop, early in late winter or spring transferred water use from vegetative stages to flowering and post-flowering stages increasing crop water use later in the season. Root length and root length density were reduced by pre-flowering mean temperatures lower than 20 °C, indicating a need to increase cold tolerance for early sowing. The higher grain numbers in early sown crops were related to higher grain numbers in tillers. The EMI derived index of root activity has a potential in the development of high throughput root phenotyping applications.

A case-cohort study of per- and polyfluoroalkyl substance concentrations and incident prostate cancer in the cancer prevention Study-II LifeLink cohort study - Alyssa N. Troeschel; Lauren R. Teras; James M. Hodge; Juan Rodriguez; Ying Wang; Johnni Daniel; W. Ryan Diver; Andrea Winquist (Environmental Research, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Paleoclimatic implications of a vascular plant from the lowermost Itararé Group - Daniel Sedorko; Rafael Spiekermann; Rafael Costa da Silva; Renato Rodriguez Cabral Ramos; Claudio Limeira Mello; Joseline Manfroi; Paula Andrea Sucerquia; Bruno Lopes Gomes; André Jasper (Journal of South American Earth Sciences, 2024)

Exploring the nexus of urban form, transport, environment and health in large-scale urban studies: A state-of-the-art scoping review - Georgia M.C. Dyer; Sasha Khomenko; Deepti Adlakha; Susan Anenberg; Martin Behnisch; Geoff Boeing; Manuel Esperon-Rodriguez; Antonio Gasparrini; Haneen Khreis; Michelle C. Kondo; Pierre Masselot; Robert I. McDonald; et al. (Environmental Research, 2024)

First Record of Conotrachelus quadrilineatus Champion, 1904 (Coleoptera: Curculionidae: Molytinae) Damaging Beans in South America - Daniel A. Baron-Ortiz; Fredy A. Rodriguez-Cruz; Oscar F. Santos-Amaya (Neotropical Entomology, 2024)
Common bean ( Phaseolus vulgaris L.) is the most important legume used for direct human consumption in Latin America, with an increasing expansion of cultivated areas in recent years. Here, we report the first occurrence of Conotrachelus quadrilineatus Champion, 1904 (Coleoptera: Curculionidae: Molytinae) feeding on bean in South America. Larvae and adults of C. quadrilineatus were observed during the first half of 2022, severely affecting the plantations of 20 bean farmers in the municipality of Garcia-Rovira, Santander Colombia. It is necessary to describe and quantify the damage of C. quadrilineatus in bean crops, as well as to study its bioecology.

Depositional processes in a shale-dominated Devonian succession: Sedimentary facies and trace fossil integrated analysis - Josiane Branco Plantz; Daniel Sedorko; Thiago Gonçalves Carelli; Renato Rodriguez Cabral Ramos; Leonardo Borghi (Sedimentary Geology, 2024)

Improving physiological simulations in seasonally dry tropical forests with limited measurements - Iago Alvarenga e Silva; Daniel Andres Rodriguez; Rogério Pinto Espíndola (Theoretical and Applied Climatology, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Decision-making in open carpooling programs: Perspectives of drivers versus passengers - Willis Simancas; Cristian Vinasco; Daniel Rosas-Satizábal; Hernan Alberto Ortiz-Ramirez; Alvaro Rodriguez-Valencia (Travel Behaviour and Society, 2024)

Electrical resilience assessment of a building operating at low voltage - Rusber Rodriguez; German Osma; David Bouquain; Gabriel Ordoñez; Damien Paire; Javier Solano; Robin Roche; Daniel Hissel (Energy and Buildings, 2024)

Tree-ring wood density reveals differentiated hydroclimatic interactions in species along a bioclimatic gradient - Marín Pompa-García; Eduardo Daniel Vivar-Vivar; Bruna Hornink; José Alexis Martínez-Rivas; Daigard Ricardo Ortega-Rodriguez; Mario Tomazello-Filho (Dendrochronologia, 2024)

Development and growth of bovine calves demi-embryos - Amada E. Ynsaurralde-Rivolta; Andres Rogberg-Muñoz; Sebastian Lopez-Valiente; Sebastian Maresca; Alejandro Rodriguez; Carlos Munar; Sebastian Munilla-Leguizamón; Franco A. Dellavalle; Daniel Salamone (Animal Reproduction Science, 2024)

Comparing Transcriptomic Points of Departure to Apical Effect Concentrations For Larval Fathead Minnow Exposed to Chemicals with Four Different Modes Of Action - Kevin Flynn; Michelle Le; Monique Hazemi; Adam Biales; David C. Bencic; Brett R. Blackwell; Kendra Bush; Robert Flick; John X. Hoang; John Martinson; Mackenzie Morshead; Kelvin Santana Rodriguez; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Development of Catharanthus callus cell lines for indole-derived alkaloids production - Daniel Arturo Zavala-Ortiz; María Ines Infanzón-Rodríguez; Javier Gomez-Rodriguez; Diana Laura Palacios-Pérez; Carlos Augusto Ledesma-Escobar; María Guadalupe Aguilar-Uscanga (South African Journal of Botany, 2024)

Short-term associations between fine particulate air pollution and cardiovascular and respiratory mortality in 337 cities in Latin America - Nelson Gouveia; Jordan L. Rodriguez-Hernandez; Josiah L. Kephart; Ana Ortigoza; Ricardo Morales Betancourt; Jose Luis Texcalac Sangrador; Daniel A. Rodriguez; Ana V. Diez Roux; Brisa Sanchez; Goro Yamada (Science of The Total Environment, 2024)

Size at Sexual Maturity of Deep-Sea Unexploited Caribbean Metanephrops binghami (Boone, 1927) and Overexploited Mediterranean Nephrops norvegicus (Linnaeus, 1758) Using Morphometric and Gonadal Staging Approaches - Jorge Paramo; Alfredo Rodriguez; Juliana Quevedo Zabala; Joan B. Company; Daniel Pérez; Maria Vigo; Ricardo Santos-Bethencourt; Jacopo Aguzzi; Nixon Bahamon (Fishes, 2024)
The deep-sea Caribbean lobster (Metanephrops binghami) and the Norway lobster (Nephrops norvegicus) are Nephropidae species of high commercial interest. Although the first one still remains unexploited, the second is overexploited in the Mediterranean Sea. For effective fisheries management, size at sexual maturity is an essential indicator to protect immature individuals from exploitation. The estimation of this indicator can, however, be biased due to the difficulty of differentiating juveniles from adults by their size structure due to the natural process of molting. This study aims to estimate the size at sexual maturity of M. binghami and N. norvegicus females by comparing the effectiveness of the morphometric method versus the macroscopic evaluation of gonad maturity. Samples of M. binghami were collected from the Colombian Caribbean Sea in August and December 2009, March and May 2010, and August 2020 to May 2021. Samples of N. norvegicus were collected from the northwestern Mediterranean Sea from 2019 to 2022. Similar sizes at sexual maturity were found for M. binghami between the morphometric approach (ranging from 28.6 to 33.9 mm cephalothorax length, CL) and the gonadal staging approach (31.4 mm CL). Conversely, for N. norvegicus, the morphometric approach yielded higher measurements (between 27.2 and 30.4 mm CL) than the gonadal approach (26.0 mm CL). This discrepancy might stem from the intense fishing overexploitation conditions of N. norvergicus, leading to a physiological adaptation that enables earlier gonadal maturation at faster rates than morphometric adaptation. Further research is required to elucidate these discrepancies and the effect of overexploitation on physiological (i.e., mature gonads) and functional maturity (i.e., capacity to brood eggs at a larger size).

Experimental investigation using demountable steel-concrete composite reduced web section (RWS) connections under cyclic loads - Fahad Falah Almutairi; Konstantinos Daniel Tsavdaridis; Andres Alonso-Rodriguez; Iman Hajirasouliha (Bulletin of Earthquake Engineering, 2024)
This paper presents an experimental study of demountable steel-concrete composite reduced web section (RWS) connections for use in seismic areas. Four composite connection specimens were subjected to sagging and hogging moments to investigate the performance of RWS connections under reversible actions. For such purpose, a single web opening was created near the beam-column joint. Focus was made on the effects of perforation location and composite beam-slab action induced by bolted shear studs within the protected zone. Results indicate that employing RWS connections for seismic retrofit is a viable solution capable of achieving a performance similar to that observed for RBS connections in new buildings. Notably, a Vierendeel Mechanism is formed, allowing for plasticity development in the beam. All RWS connections were capable of achieving an interstory drift larger than 4%, thereby complying with the performance targets set by ANSI/AISC 358-16, ANSI/AISC 341-16 and EC8. Moreover, the deformation of beam-slab shear-transfer bolts was small enough to allow for disassembly after the tests, indicating that the proposed solution could enable reuse and post-earthquake retrofitting.

Crustal structure of the Western Azuero Peninsula, Panama: Insights into the structure of accretionary complexes and forearc ophiolites - Carolina Ortiz-Guerrero; Camilo Montes; David W. Farris; Catalina Agudelo; Margarita Ariza Acero; Juliana Ayala; Jose David Avellaneda; Alejandro Cortes-Calderon; Esteban Gaitan; Sebastian Garzon; Daniel Gongora-Blanco; Nubia Andrea Jara; et al. (International Geology Review, 2024)

Inter-basin water transfers under changing climate and land use: Assessing water security and hydropower in the Paraíba do Sul River basin, Brazil - Ana Carolina da Encarnação Paiva; Minella Martins; Erica Acioli Canamary; Daniel Andres Rodriguez; Javier Tomasella (Journal of South American Earth Sciences, 2024)

Long-range transport and microscopy analysis of Sangay volcanic ashes in Ecuador - Daniel Moran-Zuloaga; Wilson Merchan-Merchan; Emilio Rodriguez-Caballero; Maurizio Mulas; Philip Hernick (Air Quality, Atmosphere & Health, 2024)
This study aims to conduct a spatiotemporal analysis of the long-range transportation of volcanic ashes that originates from the eruption of the Sangay volcano and reached Guayaquil during the months of June 2020; September 2020; and April 2021. The particulate matter data (PM 2.5 ) was obtained using a low-cost air quality sensor. During the wet season of 2020 (Jan–May), PM 2.5 average concentrations were 6 ± 2 μg m −3 while during the dry season of 2020 (July–Nov), PM 2.5 average concentrations were 16 ± 3 μg m −3 in Guayaquil. The most prominent plumes occurred on September 20th of 2020, a month with no rain but high wind speeds created by the Andes Mountain topography to the coast. During this event, PM 2.5 concentrations started at 12:00 UTC-5 in a volcanic plume event that lasted 4 h with a maximum peak of 133 + 40 μg m −3 . Electron microscopy of selected samples showed that the ashes of the three eruptions may differ in size and morphology. EDX analysis reveals that the ash contains certain elements—C, Si, Na, Mg, Al, Ca, S, and Fe—in similar proportions. In summary, this study remarks on the meteorological role and the long-range transport of Sangay volcanic ashes.

Recent greening may curb urban warming in Latin American cities of better economic conditions - Yang Ju; Iryna Dronova; Daniel A. Rodriguez; Maryia Bakhtsiyarava; Irene Farah (Landscape and Urban Planning, 2023)

Incorporating environmental covariates to explore genotype × environment × management (G × E × M) interactions: A one-stage predictive model - Michael H. Mumford; Clayton R. Forknall; Daniel Rodriguez; Joseph X. Eyre; Alison M. Kelly (Field Crops Research, 2023)

Impacts of the land use and land-cover changes on local hydroclimate in southwestern Amazon - Isabel L. Pilotto; Daniel A. Rodriguez; Sin-Chan Chou; Lucas Garofolo; Jorge L. Gomes (Climate Dynamics, 2023)

Identification of nutritional biomarkers through highly sensitive and chemoselective metabolomics - Weifeng Lin; Kiana Mellinghaus; Ana Rodriguez-Mateos; Daniel Globisch (Food Chemistry, 2023)

Integrity of the nucleus basalis of meynert and self-reported cognitive dysfunction during wearing-off periods in parkinson’s disease - Daniel H. Lench; Travis H. Turner; Emma Wetmore; Federico J. Rodriguez-Porcel; Gonzalo J. Revuelta (Brain Imaging and Behavior, 2023)

Smoking, blood DNA methylation sites and lung cancer risk - Arce Domingo-Relloso; Roby Joehanes; Zulema Rodriguez-Hernandez; Lies Lahousse; Karin Haack; M. Daniele Fallin; Miguel Herreros-Martinez; Jason G. Umans; Lyle G. Best; Tianxiao Huan; Chunyu Liu; Jiantao Ma; et al. (Environmental Pollution, 2023)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Ambient temperature modulates body weight changes in patients with advanced oncological diseases and anorexia cachexia syndrome - Paloma Encinas; Jose Luis Rodriguez-Arias; Luis Miguel Luengo Pérez; Daniel Cortizo; Emilio Gutierrez (International Journal of Biometeorology, 2023)
Objective To assess the impact of ambient temperature (AT) on the evolution of bodyweight in patients with heterogeneous types of cancer in advanced stages of the disease (stages III and IV) and anorexia- cachexia syndrome (ACS). Methods A prospective naturalistic multicenter study of patients undergoing oncological treatment at four hospitals during a three-year period (2017–2020) in the Autonomous Community of Extremadura in southwestern Spain with a continentalized Mediterranean climate of mild and relatively rainy winters, and particularly hot and sunny summers. Bodyweight changes were obtained from the medical records of 84 oncological patients (59 men and 25 women, age range 37–91 yrs). Mean monthly AT was used to examine the association of weight changes across cold and warm bimesters -BIMs (December and January, vs. July and August), Trimesters -TRIMs (July to September vs. December to February), and Semesters -SEMs (May to October vs. November to April). Weight changes between two consecutive weight measures were categorized as weight gain, weight loss, or no weight change. Differences across cold and warm seasons were analysed using parametric (ANOVA), and nonparametric statistics (Chi-square and binomial z tests). An alpha-rate of 0.05 was used for all analyses. Results A weight loss trend was observed during BIMs cold periods in comparison to warm ones ( p 0.04). However, differences in average bodyweight were not significant. The negative impact of cold periods was more marked in men than in women, ( p = 0.05; p = 0.03, for cold vs. warm BIMs and TRIMs, respectively). In contrast, significantly higher weight gain percentages were found in women during warm TRIMs and SEMs ( p = 0.03, and p = 0.01, respectively). As for the number of patients dying during the study ( N = 56; 39 men, 17 women), there were a significant interaction between temperature (cold/warm), and mean weight F ( 1, 499) = 6.06, p = 0.01, which revealed a pattern of weight loss in the cold semester as opposed to weight gain during the warm SEM months. Conclusions AT temperature modulated body weight changes in patients with advanced oncological disease and ACS. Two main limitations of the study were the absence of information on diets as a moderating factor of weight loss/gain, and the lack of the patients’ weight measurements closest to the date of diagnosis prior to admittance to the study. As for the practical implications, it remains to be seen whether an adjunctive heat supply will serve a buffering effect on weight loss during colder seasons for patients with advanced cancer and ACS.

Miocene tropical storms: Carbonate framework approaches and geochemistry proxies in a reservoir model - Orangel Aguilera; Olga M. Oliveira De Araújo; Ricardo Tadeu Lopes; Marcelo Cohen; Dayana Alvarado Sierra; Beatriz Teixeira Guimarães; Ana Paula Linhares; Félix Rodriguez; Manuel Moreira; Rut Díaz; Hamilton Santos Gama Filho; Marcelino Jose Dos Anjos; et al. (Marine and Petroleum Geology, 2023)

A framework for the assessment of farm diversification options in broadacre agriculture - Lipy Adhikari; Adam M. Komarek; Peter de Voil; Daniel Rodriguez (Agricultural Systems, 2023)

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Does the protein structure of β-lactoglobulin impact its complex coacervation with type A gelatin and the ability of the complexes to entrap lutein? - Martin Daniel Aya Rodriguez; Danilo C. Vidotto; Ana Augusta O. Xavier; Raphaela A. Mantovani; Guilherme M. Tavares (Food Hydrocolloids, 2023)

Corrigendum to “Forest Hydrology in Chile; paste, present, and future” [J. Hydrol. 616 (2023)] - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barria; et al. (Journal of Hydrology, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Detecting volunteer cotton plants in a corn field with deep learning on UAV remote-sensing imagery - Pappu Kumar Yadav; J. Alex Thomasson; Robert Hardin; Stephen W. Searcy; Ulisses Braga-Neto; Sorin C. Popescu; Daniel E Martin; Roberto Rodriguez; Karem Meza; Juan Enciso; Jorge Solorzano Diaz; Tianyi Wang (Computers and Electronics in Agriculture, 2023)

Assessment of the environmental acceptability of potential artificial reef materials using two ecotoxicity tests: Luminescent bacteria and sea urchin embryogenesis - Jorge Santos; Eva Cifrian; Araceli Rodriguez-Romero; Adrian I. Yoris-Nobile; Elena Blanco-Fernandez; Daniel Castro-Fresno; Ana Andres (Chemosphere, 2023)

Forest hydrology in Chile: Past, present, and future - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barría; et al. (Journal of Hydrology, 2023)

Elevated Winter Stream Temperatures below Wastewater Treatment Plants Shift Reproductive Development of Female Johnny Darter Etheostoma nigrum: A Field and Histologic Approach - Catherine M. Adams; Dana L. Winkelman; Paula A. Schaffer; Daniel L. Villeneuve; Jenna E. Cavallin; Michael Ellman; Kelvin Santana Rodriguez; Ryan M. Fitzpatrick (Fishes, 2022)
River water temperatures are increasing globally, particularly in urban systems. In winter, wastewater treatment plant (WWTP) effluent inputs are of particular concern because they increase water temperatures from near freezing to ~7–15 °C. Recent laboratory studies suggest that warm overwinter temperatures impact the reproductive timing of some fishes. To evaluate winter water temperature’s influence in the wild, we sampled Johnny Darter Etheostoma nigrum from three urban South Platte River tributaries in Colorado upstream and downstream of WWTP effluent discharge sites. Fish were collected weekly during the spring spawning season of 2021 and reproductive development was determined from histological analysis of the gonads. Winter water temperatures were approximately 5–10 °C greater ~300 m downstream of the WWTP effluent compared to upstream sites, and approximately 3 °C warmer at sampling sites ~5000 m downstream of the effluent discharge. Females collected downstream of WWTP effluent experienced accelerated reproductive development compared to upstream by 1–2 weeks. Water quality, including total estrogenicity, and spring water temperatures did not appear to explain varying reproductive development. It appears that small increases in winter water temperature influence the reproductive timing in E. nigrum. Further investigations into how shifts in reproductive timing influence other population dynamics are warranted.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Conservation Policy Changes in Protected Areas on Hilltops in Brazil: Effects on Hydrological Response in a Small Watershed - Ulises Rodrigo Magdalena; Cristiane Nunes Francisco; Lucas Garofolo Lopes; Daniel Andrés Rodriguez (Water Resources Management, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Correction to: How will artificial intelligence and bioinformatics change our understanding of IgA Nephropathy in the next decade? - Roman David Bülow; Daniel Dimitrov; Peter Boor; Julio Saez-Rodriguez (Seminars in Immunopathology, 2021)
A Correction to this paper has been published: 10.1007/s00281-021-00858-9

How will artificial intelligence and bioinformatics change our understanding of IgA Nephropathy in the next decade? - Roman David Bülow; Daniel Dimitrov; Peter Boor; Julio Saez-Rodriguez (Seminars in Immunopathology, 2021)
IgA nephropathy (IgAN) is the most common glomerulonephritis. It is characterized by the deposition of immune complexes containing immunoglobulin A (IgA) in the kidney’s glomeruli, triggering an inflammatory process. In many patients, the disease has a progressive course, eventually leading to end-stage kidney disease. The current understanding of IgAN’s pathophysiology is incomplete, with the involvement of several potential players, including the mucosal immune system, the complement system, and the microbiome. Dissecting this complex pathophysiology requires an integrated analysis across molecular, cellular, and organ scales. Such data can be obtained by employing emerging technologies, including single-cell sequencing, next-generation sequencing, proteomics, and complex imaging approaches. These techniques generate complex “big data,” requiring advanced computational methods for their analyses and interpretation. Here, we introduce such methods, focusing on the broad areas of bioinformatics and artificial intelligence and discuss how they can advance our understanding of IgAN and ultimately improve patient care. The close integration of advanced experimental and computational technologies with medical and clinical expertise is essential to improve our understanding of human diseases. We argue that IgAN is a paradigmatic disease to demonstrate the value of such a multidisciplinary approach.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Sensible heat flux assessment in a complex coastal-mountain urban area in the metropolitan area of Rio de Janeiro, Brazil - Rafael João Sampaio; Daniel Andres Rodriguez; Celso Von Randow; Fabricio Polifke da Silva; Afonso Augusto Magalhães de Araújo; Otto Corrêa Rotunno Filho (Meteorology and Atmospheric Physics, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

Post-dispersal seed predation in Patagonia temperate forest depends on habitat patchiness and seed species - Luciana Motta; Agustin Vitali; Guillermo C. Amico; Daniel García; Mariano A. Rodriguez-Cabal (Plant Ecology, 2021)

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Biological production of H 2 , CH 4 and CO 2 in the deep subsurface of the Iberian Pyrite Belt - Jose L. Sanz; Nuria Rodriguez; Cristina Escudero; Daniel Carrizo; Ricardo Amils (Environmental Microbiology, 2021)
Summary Most of the terrestrial deep subsurfaces are oligotrophic environments in which some gases, mainly H 2 , CH 4 and CO 2 , play an important role as energy and/or carbon sources. In this work, we assessed their biotic and abiotic origin in samples from subsurface hard‐rock cores of the Iberian Pyrite Belt (IPB) at three different depths (414, 497 and 520 m). One set of samples was sterilized (abiotic control) and all samples were incubated under anaerobic conditions. Our results showed that H 2 , CH 4 and CO 2 remained low and constant in the sterilized controls while their levels were 4, 4.1 and 2.5 times higher respectively, in the unsterilized samples compared to the abiotic controls. The δ 13 C CH4 ‐values measured in the samples (range −31.2 to −43.0 ‰) reveals carbon isotopic signatures that are within the range for biological methane production. Possible microorganisms responsible for the biotic production of the gases were assessed by CARD‐FISH. The analysis of sequenced genomes of detected microorganisms within the subsurface of the IPB allowed to identify possible metabolic activities involved in H 2 ( Rhodoplanes , Shewanella and Desulfosporosinus ), CH 4 (Methanobacteriales) and CO 2 production. The obtained results suggest that part of the H 2 , CH 4 and CO 2 detected in the deep subsurface has a biological origin.

Productive and reproductive performance of females F1 Holstein x Gir daughters of proven bulls - Maria Dulcinéia da Costa; Alvimara Felix dos Reis; José Reinaldo Mendes Ruas; Gislane Evangelista Bispo; Vicente Ribeiro Rocha Júnior; Virgílio Mesquita Gomes; Tânia Lino Fiúza; Mary Ana Petersen Rodriguez; Mário Henrique França Mourthé; Daniel Ananias de Assis Pires (Tropical Animal Health and Production, 2021)

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

Movements of green turtles from foraging areas of the United Arab Emirates: regional habitat connectivity and use of marine protected areas - Nicolas James Pilcher; Marina A. Antonopoulou; Clara Jimena Rodriguez-Zarate; Daniel Mateos-Molina; Himansu Sekhar Das; Ibrahim Bugla; Saif Mohammed Al Ghais (Marine Biology, 2021)
Adult sea turtles migrate between foraging areas and nesting sites that may be 100 s–1000 s of km away. Little is known of the connectivity between these sites in the Arabian region for green sea turtles. We document linkages between two foraging areas in the United Arab Emirates (UAE) with key nesting sites and provide insights on effectiveness of marine protected areas for green sea turtles. Tracking 45 adult green sea turtles Chelonia mydas from foraging areas in the UAE, we show that the primary nesting destination for turtles foraging in Bu Tinah in the UAE is Ras al Hadd in Oman. The turtles use the waters of the UAE, Iran and Oman during breeding migrations and generally stay ~ 20 km off the coast, in waters 10–20 m deep except when crossing the Sea of Oman. Turtles display substantial fidelity to the original foraging sites, often traversing other known foraging sites when returning from the breeding migration. A small proportion of turtles also utilise more than one foraging site. Our data indicate that the Marawah Marine Biosphere Reserve in Abu Dhabi is broadly coincident with the foraging areas of turtles offering substantial protection from fishery activities and that the marine protected area in Ras Al Khaimah would be more effective in protecting green sea turtles if it extended offshore and along the coast. These data may contribute to targeted and effective national and international management and conservation initiatives in the Arabian region.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Ageusia and anosmia, a common sign of COVID-19? A case series from four countries - Jair Vargas-Gandica; Daniel Winter; Rainer Schnippe; Andrea G. Rodriguez-Morales; Johana Mondragon; Juan Pablo Escalera-Antezana; María del Pilar Trelles-Thorne; D. Katterine Bonilla-Aldana; Alfonso J. Rodriguez-Morales; Alberto Paniz-Mondolfi (Journal of NeuroVirology, 2020)

Amphetamine-induced striatal dopamine release in schizotypal personality disorder - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Xiaoyan Xu; Ethan G. Rothstein; Yosefa A. Modiano; Lawrence S. Kegeles; Harold W. Koenigsberg; Antonia S. New; Erin A. Hazlett; Margaret M. McClure; M. Mercedes Perez-Rodriguez; et al. (Psychopharmacology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Pelagic Sargassum spp. capture CO2 and produce calcite - Francisco Paraguay-Delgado; Caleb Carreño-Gallardo; Ivanovich Estrada-Guel; Alberto Zabala-Arceo; Harby Alexander Martinez-Rodriguez; Daniel Lardizábal-Gutierrez (Environmental Science and Pollution Research, 2020)

Downscaling projections of climate change in Sao Tome and Principe Islands, Africa - Sin Chan Chou; André de Arruda Lyra; Jorge Luís Gomes; Daniel Andrés Rodriguez; Minella Alves Martins; Nicole Costa Resende; Priscila da Silva Tavares; Claudine Pereira Dereczynski; Isabel Lopes Pilotto; Alessandro Marques Martins; Luís Felipe Alves de Carvalho; José Luiz Lima Onofre; et al. (Climate Dynamics, 2020)

Cross-transferability analysis of SSR markers developed from the American Cranberry (Vaccinium macrocarpon Ait.) to other Vaccinium species of agricultural importance - Lorraine Rodriguez-Bonilla; Jessica Rohde; Daniel Matusinec; Juan Zalapa (Genetic Resources and Crop Evolution, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

Development of Chitosan and Alginate Nanocapsules to Increase the Solubility, Permeability and Stability of Curcumin - Daniel Hernandez-Patlan; Bruno Solis-Cruz; Mario Alberto Cano-Vega; Eric Beyssac; Ghislain Garrait; Xochitl Hernandez-Velasco; Raquel Lopez-Arellano; Guillermo Tellez; Gustavo R. Rivera-Rodriguez (Journal of Pharmaceutical Innovation, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Response of the river discharge in the Tocantins River Basin, Brazil, to environmental changes and the associated effects on the energy potential - Rita Casia Silva Von Randow; Daniel Andrés Rodriguez; Javier Tomasella; Ana Paula Dutra Aguiar; Bart Kruijt; Pavel Kabat (Regional Environmental Change, 2019)

Relationships between variability in precipitation, river levels, and beef cattle production in the Brazilian Pantanal - Ana Gabriela de J. Araujo; Guillermo O. Obregón; Gilvan Sampaio; Antonio Miguel V. Monteiro; Luiz Tadeu da Silva; Balbina Soriano; Carlos Padovani; Daniel Andres Rodriguez; Jelena Maksic; José Felipe Silva Farias (Wetlands Ecology and Management, 2018)

Cognitive Impairment and Brain and Peripheral Alterations in a Murine Model of Intraventricular Hemorrhage in the Preterm Newborn - Antonio Segado-Arenas; Carmen Infante-Garcia; Isabel Benavente-Fernandez; Daniel Sanchez-Sotano; Juan Jose Ramos-Rodriguez; Almudena Alonso-Ojembarrena; Simon Lubian-Lopez; Monica Garcia-Alloza (Molecular Neurobiology, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

Stochastic evaluation of the impact of sewer inlets’ hydraulic capacity on urban pluvial flooding - João P. Leitão; Nuno E. Simões; Rui Daniel Pina; Susana Ochoa-Rodriguez; Christian Onof; Alfeu Sá Marques (Stochastic Environmental Research and Risk Assessment, 2017)

Wnts Are Expressed in the Ependymal Region of the Adult Spinal Cord - Carlos Gonzalez-Fernandez; Angel Arevalo-Martin; Beatriz Paniagua-Torija; Isidro Ferrer; Francisco J. Rodriguez; Daniel Garcia-Ovejero (Molecular Neurobiology, 2017)

L-Type Calcium Channels Modulation by Estradiol - Nelson E. Vega-Vela; Daniel Osorio; Marco Avila-Rodriguez; Janneth Gonzalez; Luis Miguel García-Segura; Valentina Echeverria; George E. Barreto (Molecular Neurobiology, 2017)

Satellite Remote Sensing for Coastal Management: A Review of Successful Applications - Matthew J. McCarthy; Kaitlyn E. Colna; Mahmoud M. El-Mezayen; Abdiel E. Laureano-Rosario; Pablo Méndez-Lázaro; Daniel B. Otis; Gerardo Toro-Farmer; Maria Vega-Rodriguez; Frank E. Muller-Karger (Environmental Management, 2017)

Small shifts in microsite occupation could mitigate climate change consequences for mountain top endemics: a test analyzing saxicolous lichen distribution patterns - Juan Manuel Rodriguez; Daniel Renison; Edith Filippini; Cecilia Estrabou (Biodiversity and Conservation, 2017)

Regional modeling of climate change impacts on smallholder agriculture and ecosystems in Central America - Lee Hannah; Camila I. Donatti; Celia A. Harvey; Eric Alfaro; Daniel Andres Rodriguez; Claudia Bouroncle; Edwin Castellanos; Freddy Diaz; Emily Fung; Hugo G. Hidalgo; Pablo Imbach; Peter Läderach; et al. (Climatic Change, 2017)

Projections of climate change impacts on central America tropical rainforest - André Lyra; Pablo Imbach; Daniel Rodriguez; Sin Chan Chou; Selena Georgiou; Lucas Garofolo (Climatic Change, 2017)
Tropical rainforest plays an important role in the global carbon cycle, accounting for a large part of global net primary productivity and contributing to CO 2 sequestration. The objective of this work is to simulate potential changes in the rainforest biome in Central America subject to anthropogenic climate change under two emissions scenarios, RCP4.5 and RCP8.5. The use of a dynamic vegetation model and climate change scenarios is an approach to investigate, assess or anticipate how biomes respond to climate change. In this work, the Inland dynamic vegetation model was driven by the Eta regional climate model simulations. These simulations accept boundary conditions from HadGEM2-ES runs in the two emissions scenarios. The possible consequences of regional climate change on vegetation properties, such as biomass, net primary production and changes in forest extent and distribution, were investigated. The Inland model projections show reductions in tropical forest cover in both scenarios. The reduction of tropical forest cover is greater in RCP8.5. The Inland model projects biomass increases where tropical forest remains due to the CO 2 fertilization effect. The future distribution of predominant vegetation shows that some areas of tropical rainforest in Central America are replaced by savannah and grassland in RCP4.5. Inland projections under both RCP4.5 and RCP8.5 show a net primary productivity reduction trend due to significant tropical forest reduction, temperature increase, precipitation reduction and dry spell increments, despite the biomass increases in some areas of Costa Rica and Panama. This study may provide guidance to adaptation studies of climate change impacts on the tropical rainforests in Central America.

Blade life span, structural investment, and nutrient allocation in giant kelp - Gabriel E. Rodriguez; Daniel C. Reed; Sally J. Holbrook (Oecologia, 2016)

On the ability of large-scale hydrological models to simulate land use and land cover change impacts in Amazonian basins - Daniel Andres Rodriguez; Javier Tomasella (Hydrological Sciences Journal, 2016)

Novel Approaches in Astrocyte Protection: from Experimental Methods to Computational Approaches - Daniel Garzón; Ricardo Cabezas; Nelson Vega; Marcos Ávila-Rodriguez; Janneth Gonzalez; Rosa Margarita Gómez; Valentina Echeverria; Gjumrakch Aliev; George E. Barreto (Journal of Molecular Neuroscience, 2016)

Effect of phloroglucinol on rooting and in vitro acclimatization of papaya (Carica papaya L. var. Maradol Roja) - Laisyn Posada Pérez; Yenny Padrón Montesinos; Justo González Olmedo; Raúl Barbón Rodriguez; Romelio Rodríguez Sánchez; Osvaldo Norman Montenegro; Rene Carlos Rodriguez Escriba; Dion Daniels; Rafael Gómez-Kosky (In Vitro Cellular & Developmental Biology - Plant, 2016)

Cobia ( Rachycentron canadum ): A Selected Annotated Bibliography on Aquaculture, General Biology and Fisheries 1967–2015 - Uriel Rodriguez Estrada; Fanny Ayumi Yasumaru; Albert G. J. Tacon; Daniel Lemos (Reviews in Fisheries Science & Aquaculture, 2016)

Root plasticity and its functional roles were triggered by water deficit but not by the resulting changes in the forms of soil N in rice - Thiem Thi Tran; Mana Kano-Nakata; Roel Rodriguez Suralta; Daniel Menge; Shiro Mitsuya; Yoshiaki Inukai; Akira Yamauchi (Plant and Soil, 2015)

Understanding the Role of the Biological Pump in the Global Carbon Cycle: An Imperative for Ocean Science - Susumu Honjo; Timothy Eglinton; Craig Taylor; Kevin Ulmer; Stefan Sievert; Astrid Bracher; Christopher German; Virginia Edgcomb; Roger Francois; M. Debora Iglesias-Rodriguez; Benjamin Van Mooy; Daniel Rapeta (Oceanography, 2014)

Evaluation of Mangrove Cover Changes in Mexico During the 1970–2005 Period - Luis Valderrama; Carlos Troche; Ma. Teresa Rodriguez; Daniel Marquez; Berenice Vázquez; Samuel Velázquez; Alma Vázquez; Ma. Isabel Cruz; Rainer Ressl (Wetlands, 2014)

A set of microsatellite markers for the threatened Murray hardyhead, Craterocephalus fluviatilis (Pisces: Atherinidae) from the southern Murray–Darling Basin - Clara J. Rodriguez-Zarate; Daniel C. Carvalho; Michael P. Hammer; Luciano B. Beheregaray (Conservation Genetics Resources, 2014)

Impacts of landscape fragmentation on simulated precipitation fields in the Amazonian sub-basin of Ji-Paraná using the Eta model - Daniel Andres Rodriguez; Sin Chan Chou; Javier Tomasella; Eleonora M. C. Demaria (Theoretical and Applied Climatology, 2014)

Temperature Performance of Different Pervious Pavements: Rainwater Harvesting for Energy Recovery Purposes - Amaya V. Novo; Joseba R. Bayon; Daniel Castro-Fresno; Jorge Rodriguez-Hernandez (Water Resources Management, 2013)

Bivalve distribution in hydrographic regions in South America: historical overview and conservation - Daniel Pereira; Maria Cristina Dreher Mansur; Leandro D. S. Duarte; Arthur Schramm de Oliveira; Daniel Mansur Pimpão; Cláudia Tasso Callil; Cristián Ituarte; Esperanza Parada; Santiago Peredo; Gustavo Darrigran; Fabrizio Scarabino; Cristhian Clavijo; et al. (Hydrobiologia, 2013)

Experiments using new initial soil moisture conditions and soil map in the Eta model over La Plata Basin - Moira E. Doyle; Javier Tomasella; Daniel A. Rodriguez; Sin Chan Chou (Meteorology and Atmospheric Physics, 2013)

The importance of progressive senescence in the biomass dynamics of giant kelp ( Macrocystis pyrifera ) - Gabriel E. Rodriguez; Andrew Rassweiler; Daniel C. Reed; Sally J. Holbrook (Ecology, 2013)
Temporal variation in primary producer biomass has profound effects on the structure and function of the surrounding ecological community. The giant kelp ( Macrocystis pyrifera ) exhibits strong intra‐annual variation in biomass density, which is better explained by the demographic rates of fronds than by those of whole plants. To better understand the processes controlling the dynamics of giant kelp fronds we collected monthly time‐series data of frond initiation and survival. These data were used to determine how frond loss and frond initiation rates were predicted by factors thought to affect the growth and survival of Macrocystis , including external environmental factors (i.e., wave height, day length, temperature, nutrient concentration, and neighborhood density) and intrinsic biological characteristics (i.e., frond age, plant size, and nutritional status). Our results revealed that frond dynamics were better explained by intrinsic biological processes rather than external environmental factors. A metric of frond age structure that incorporated progressive senescence was the best predictor of frond loss rate, accounting for 58% of the explained variation in frond loss. A similar analysis revealed that frond age structure was also the single best predictor of frond initiation rate, accounting for 46% of the explained variation. To further examine the importance of senescence in biomass dynamics, we used frond age‐dependent mortality and frond initiation rates to predict biomass in subsequent months and found that the model explained 73% of the observed variation in biomass at our sites. Vegetation dynamics of many species including giant kelp are often considered largely in the context of external controls on resource availability and physical disturbance. Our results indicate that investigations of the processes controlling vegetation dynamics may benefit greatly from the inclusion of intrinsic biological factors such as age‐dependent mortality and growth, which can outweigh the effects of external forcing in accounting for fluctuations in vegetation biomass.

First Report of Microcystins and Anatoxin-a Co-occurrence in San Roque Reservoir (Córdoba, Argentina) - Marcia Ruiz; Lucas Galanti; Ana Laura Ruibal; María Ines Rodriguez; Daniel Alberto Wunderlin; María Valeria Amé (Water, Air, & Soil Pollution, 2013)

The droughts of 1997 and 2005 in Amazonia: floodplain hydrology and its potential ecological and human impacts - Javier Tomasella; Patrícia F. Pinho; Laura S. Borma; José A. Marengo; Carlos A. Nobre; Olga R. F. O. Bittencourt; Maria C. R. Prado; Daniel A. Rodriguez; Luz A. Cuartas (Climatic Change, 2013)

Overestimation of establishment success of non-native birds in Hawaii and Britain - Mariano A. Rodriguez-Cabal; Mark Williamson; Daniel Simberloff (Biological Invasions, 2013)

Characterization of CCDC28B reveals its role in ciliogenesis and provides insight to understand its modifier effect on Bardet–Biedl syndrome - Magdalena Cardenas-Rodriguez; Daniel P. S. Osborn; Florencia Irigoín; Martín Graña; Héctor Romero; Philip L. Beales; Jose L. Badano (Human Genetics, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Land Suitability Assessment in the Catchment Area of Four Southwestern Atlantic Coastal Lagoons: Multicriteria and Optimization Modeling - Lorena Rodriguez-Gallego; Marcel Achkar; Daniel Conde (Environmental Management, 2012)

The Cassava Genome: Current Progress, Future Directions - Simon Prochnik; Pradeep Reddy Marri; Brian Desany; Pablo D. Rabinowicz; Chinnappa Kodira; Mohammed Mohiuddin; Fausto Rodriguez; Claude Fauquet; Joseph Tohme; Timothy Harkins; Daniel S. Rokhsar; Steve Rounsley (Tropical Plant Biology, 2012)

CIGB-300, a synthetic peptide-based drug that targets the CK2 phosphoaceptor domain. Translational and clinical research - Silvio E. Perea; Idania Baladron; Yanelda Garcia; Yasser Perera; Adlin Lopez; Jorge L. Soriano; Noyde Batista; Aley Palau; Ignacio Hernández; Hernán Farina; Idrian Garcia; Lidia Gonzalez; et al. (Molecular and Cellular Biochemistry, 2011)

Analysis and Contrast of Different Pervious Pavements for Management of Storm-Water in a Parking Area in Northern Spain - Elena Gomez-Ullate; Elena Castillo-Lopez; Daniel Castro-Fresno; Joseba Rodriguez Bayon (Water Resources Management, 2011)

An Effective Approach to Rehabilitate Damaged Barrier System Against Piping and Contaminant Flow - David Washington; Daniel Rodriguez; Vincent Ogunro (Geotechnical and Geological Engineering, 2011)

Increasing anthraquinone production by overexpression of 1-deoxy-d-xylulose-5-phosphate synthase in transgenic cell suspension cultures of Morinda citrifolia - Carla Quevedo; María Perassolo; Eugenia Alechine; Daniel Corach; Ana María Giulietti; Julián Rodriguez Talou (Biotechnology Letters, 2010)

Recapture processes and biological inference in monitoring burrow-nesting seabirds - Ana Sanz-Aguilar; Giacomo Tavecchia; Eduardo Minguez; Bruno Massa; Fabio Lo Valvo; Gustavo A. Ballesteros; Gonzalo G. Barberá; Jose Francisco Amengual; Ana Rodriguez; Miguel McMinn; Daniel Oro (Journal of Ornithology, 2010)

Effects of nutrient and temperature on degradation of petroleum hydrocarbons in sub-Antarctic coastal seawater - Daniel Delille; Emilien Pelletier; Arturo Rodriguez-Blanco; Jean-Francois Ghiglione (Polar Biology, 2009)

Enhancement of the antioxidants ergothioneine and selenium in Pleurotus eryngii var. eryngii basidiomata through cultural practices - Alma E. Rodriguez Estrada; Hyun-Ju Lee; Robert B. Beelman; Maria del Mar Jimenez-Gasco; Daniel J. Royse (World Journal of Microbiology and Biotechnology, 2009)

Sex Pheromone of the Scarab Beetle Phyllophaga (Phytalus) georgiana (Horn) - Paul S. Robbins; Satoshi Nojima; Sridhar Polavarapu; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Robert J. Holdcraft; Nancy H. Consolie; Daniel C. Peck; Wendell L. Roelofs (Journal of Chemical Ecology, 2009)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

New selective ligands of human cloned melatonin MT1 and MT2 receptors - Valérie Audinot; François Mailliet; Chantal Lahaye-Brasseur; Anne Bonnaud; Aude Le Gall; Christophe Amossé; Sandra Dromaint; Marianne Rodriguez; Nadine Nagel; Jean-Pierre Galizzi; Benoît Malpaux; Gérald Guillaumet; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Patterns of inpatient surgeries for the top four cancers in the United States, National Hospital Discharge Survey, 1988–95 - Phyllis A. Wingo; Jodie L. Guest; LaMar McGinnis; Daniel S. Miller; Carmen Rodriguez; Cheryll J. Cardinez; Brian Morrow; Michael J. Thun (Cancer Causes & Control, 2000)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)